2018
DOI: 10.1177/0031512518767755
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Portuguese Version of the Amputee Body Image Scale: Cultural Adaptation and a Psychometric Analysis

Abstract: Body image adjustments after a limb loss are essential to rehabilitation. This study evaluated the psychometric properties of the Brazilian Portuguese version of the Amputee Body Image Scale (ABIS). We analyzed data from a nonprobability sample of 100 participants (71% men, mean age 48.26 ± 18.35 years) by using a confirmatory factor analysis with partial least square path modeling. We evaluated the structural model by using Pearson's coefficient of determination, path coefficients, indicator of Stone-Geisser,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
(80 reference statements)
0
4
1
3
Order By: Relevance
“…41 A imagem corporal da pessoa com deficiência é modelada nesse contexto de interações e reações a partir de um corpo diferente da norma, que exerce sua função de locomoção parcialmente diferente -especialmente quando não ocorreu a protetização. 33 Ademais, há modificações na imagem corporal decorrentes de reajuste da representação mental do corpo após a lesão nervosa decorrente da amputação -seja ela de causa traumática ou circulatória. 42 Esta população se depara então com o desafio de recuperar as funções do corpo e aceitar perdas e alterações da aparência inveitáveis.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…41 A imagem corporal da pessoa com deficiência é modelada nesse contexto de interações e reações a partir de um corpo diferente da norma, que exerce sua função de locomoção parcialmente diferente -especialmente quando não ocorreu a protetização. 33 Ademais, há modificações na imagem corporal decorrentes de reajuste da representação mental do corpo após a lesão nervosa decorrente da amputação -seja ela de causa traumática ou circulatória. 42 Esta população se depara então com o desafio de recuperar as funções do corpo e aceitar perdas e alterações da aparência inveitáveis.…”
Section: Discussionunclassified
“…42 Esta população se depara então com o desafio de recuperar as funções do corpo e aceitar perdas e alterações da aparência inveitáveis. 33,43 Dado essa dinâmica no desenvolvimento da imagem corporal característico da pessoa com deficiência, entendemos que o baixo valor de AVE encontrado pode ser um indicativo de ausência de variáveis observáveis para mensurar especificamente a experiência da amputação e ansiedade físico-social, pois os indicadores são pertinentes, mas não estão representando tão eficazmente o constructo.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The sample size was calculated using the G*Power software (version G*Power 3.1.9.2). We established according to previous studies [26] the following parameters to obtain the sample size using a correlation model: two tails, ρ H1 of 0.8, an error alpha of 0.05, a power of 0.95, and a minimally acceptable ρ H0 of 0.4, resulting in a sample size requirement of 31 participants [13,[20][21][22].…”
Section: Participantsmentioning
confidence: 99%
“…Breakey's original study [11] showed a Cronbach's alpha of 0.88 and good and significant concurrent validity with scales of anxiety, depression, self-esteem, and life satisfaction. It is currently validated in Portuguese, French, Chinese and Turkish [13,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%